Shikonin Inhibits APC-mutant Colon Cancer via Wnt/β-catenin Signaling - Lizhe CHEN; Bojun WANG; Qing GONG; Xue ZHANG; Xisong KE (Zhongliu Fangzhi Yanjiu, 2024)
Objective To identify small molecule inhibitors of APC-mutant colon cancer and provide lead compounds for targeted therapy of colon cancer. MethodsAPC-mutant colon cancer cell lines that stably express 7*Tcf-GFP/SV40-Cherry (7TGC) dual fluorescence reporter system was constructed for small-molecule inhibitor screening. Cell viability, colony formation, EdU incorporation, and xenograft tumor assay were used to evaluate the inhibitory effect of these inhibitors on APC-mutant colon cancer in vitro and in vivo. Western blot and co-immunoprecipitation assays were used to explore the molecular mechanism. ResultsFour small molecules that inhibited Wnt activity in APC-mutant colon cancer cells were discovered. Shikonin exhibited significant inhibition of cell viability and proliferation while inducing apoptosis of APC-mutant colon cancer cells. Xenograft tumor assay demonstrated that shikonin significantly reduced tumor growth in vivo. Furthermore, Western blot and co-immunoprecipitation assays revealed that shikonin markedly decreased β-catenin levels. ConclusionShikonin effectively inhibits Wnt activity and suppresses tumor growth in APC-mutant colon cancer.